ANALISIS PERAN TANGGUNG JAWAB DALAM MENINGKATKAN KINERJA JASABONGKAR MUAT DI PELABUHAN TANJUNG PRIOK (STUDI KASUS DI PT. BANDAR KRIDA JASINDO) - Adit Fikriansyah; Achsanul Nashir (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The main issue arise from the human resources’ role who participate in stevedoring process and management documents to improve the performance process of transporting goods at the Port. Stevedoring activities are implemented with performance responsibilities. The purpose of this study is to analyze the responsibility role in improving the stevedoring performances at Tanjung Bulek Port (case study of PT. BANDAR KRIDA JASINDO); exploretheobstacles facedby PT. BANDAR KRIDA JASINDO to improve their stevedoring performances; and to inspect the solutions from PT. BANDAR KRIDA JASINDO to tackle the obstacles. From the study results, it can be concluded that the cargo handling process is a stevedoring performance, which including: Ioad/ unload and receiving/ shipping activities. In terms of the responsibility role to improve the human resources' performances in stevedoring process, herein referred to PT. BANDAR KRIDA JASINDO. Stevedore companies only provides services (human resources) for the cargo activities from warehouse to and/or from a ship. They are responsible to load or offload cargo on board at the Port warehouse.